(untitled) (Eurasian Journal of Ecology, 2017)
The integument of a human body and animals can damage or destroy many substances having the chemical nature. Violations of integrity of integuments can occur under the influence of various factors. The chemical burn of skin is especially aggressive. It can be caused by chemicals and means on their basis. Chemical burns result from influence of acids, alkalis and aggressive substances. A chemical burn of skin of various parts differ in acids, alkalis or salts of heavy metals on expressiveness degree. Interaction of chemical with protoplasm of cells of tissues is characteristic of them. At effect of acids there is a dehydration of skin which is followed by allocation of heat and overheating of tissues that leads to coagulation of proteins and formation of a dense dry scab. At long influence of elements on integuments, there is a violation of integrity of the last. Extent of defeat depends on concentration of harmful substance and duration of his stay on the surface of skin. Even the low-concentrated solutions can become the cause of a burn if in time not to notice them. After hit of substance on skin chemical reaction is formed. It causes destruction of proteinaceous structures of skin, and membrane phospholipids. In this case on a surface there are wounds, inflammatory process. Hit of aggressive substance on a surface of an epithelium is resulted by the local chemical reaction leading to a destruction of dermal proteins, phospholipids of membranes. Morphological changes are supplemented with an ulceration of wounds and development of inflammatory process. All this in total gives an overall picture of the corrosive burn which is shown one of four degrees. In recent years considerably interest of researchers in search of the new materials suitable for use in the medical purposes, in particular nanosorbents grew. By the present moment approaches to treatment of wounds of a skin are developed. In this regard, undoubted interest for the experts working in the field represents our research which was referred on studying of local changes of structure of a skin after influence of a chemical factor with use of medical bandages, possessing antimicrobial action at the expense of a carbonaceous fiber, activly deleting a pathological microflora from a wound. This scientific experiment pursued the aim to give a comparative assessment to efficiency of use of a new method for treatment of combustions of a skin a medical bandage with a sorbent No. 1, No. 2. The sorbent bandages was a part No. 1 vitamin A, E, the dimined powder 3 gr., camphoric oil of 1 ml, and structure No. 2 the sorbent bandages consisted of the dimined powder 3gr., olive oil of 1 ml., vaselinum of 1 g. Key words: organs, destruction, enterosorbent, histology, morphology, necrosis, pathology